Nurses’ experience of using platform for phlebitis assessment based on telemedicine consultation system: a qualitative descriptive study - Thangkratok, Pramote; Pongpirul, Krit; Sriratanaban, Jiruth (Jurnal Ners, 2025)
Introduction: Current methods for assessing phlebitis rely on nurses' experiences. Integrating advanced systems, such as a Clinical Decision Support System and a Telemedicine Consultation System, is essential for more comprehensive and expert-driven diagnosis and treatment recommendations. This study explored nurses' experiences using a platform for phlebitis assessment based on a telemedicine consultation system. Methods: A qualitative study based on constructivist theory was conducted using focus group interviews with 12 registered nurses recruited from a community hospital in Thailand, between November 2022 and March 2023. The interviews were then recorded and transcribed. Data analysis followed Miles and Huberman's framework, which comprised three stages: (1) data reduction, involving the selection, organization, and coding of key data; (2) data display, structuring the data into themes to identify patterns; and (3) conclusion drawing and verification to ensure accuracy and validity through systematic comparison and cross-checking. Results: Four themes emerged: accuracy, referring to the precision of the assessments; feasibility, which pertains to how practical the system is for daily clinical use; propriety, concerning ethical and professional considerations such as patient confidentiality and alignment with nursing practices; and utility, evaluating the overall usefulness and value of the platform in enhancing assessment efficiency. Conclusions: The platform for phlebitis assessment based on the telemedicine consultation system can accurately evaluate and diagnose phlebitis. It is suitable for practical use in clinical settings and can improve patient care quality.